Intramuscular injection of alfaxalone in combination with butorphanol for sedation in cats. (July 2017) - Deutsch, Julia; Jolliffe, Colette; Archer, Emma; Leece, Elizabeth A.
Abstract: Objective: To assess quality of sedation following intramuscular (IM) injection of two doses of alfaxalone in combination with butorphanol in cats. Study design: Prospective, randomized, 'blinded' clinical study. Animals: A total of 38 cats undergoing diagnostic imaging or noninvasive procedures. Methods: Cats were allocated randomly to be administered butorphanol 0.2 mg kg −1 combined with alfaxalone 2 mg kg −1 (group AB2) or 5 mg kg −1 (group AB5) IM. If sedation was inadequate, alfaxalone 2 mg kg −1 IM was administered and cats were excluded from further analysis. Temperament [1 (friendly) to 5 (aggressive)], response to injection, sedation score at 2, 6, 8, 15, 20, 30, 40, 50 and 60 minutes, overall sedation quality scored after data collection [1 (excellent) to 4 (inadequate)] and recovery quality were assessed. Heart rate (HR), respiratory rate ( f R ) and arterial haemoglobin saturation (SpO2 ) were recorded every 5 minutes. Groups were compared using t tests and Mann–Whitney U tests. Sedation was analysed using two-wayanova, and additional alfaxalone using Fisher's exact test ( p < 0.05). Results: Groups were similar for sex, age, body mass and response to injection. Temperament score was lower in group AB2 [2 (1–3)] compared to AB5 [3 (1–5)] ( p = 0.006). Group AB5 had better sedation at 6, 8, 20 and 30 minutes and overall sedation quality was better in AB5 [1 (1–3)], compared to AB2 [3 (1–4)] ( p = 0.0001). Additional alfaxalone was required for 11 cats in AB2 and two in AB5 ( p = 0.005). Recovery quality, HR, f R and SpO2 were similar. Seven cats required oxygen supplementation. Complete recovery times were shorter in AB2 (81.8 ± 24.3 versus 126.6 ± 33.3 minutes; p = 0.009). Twitching was the most common adverse event. Conclusions and clinical relevance: In combination with butorphanol, IM alfaxalone at 5 mg kg −1 provided better quality sedation than 2 mg kg −1 . Monitoring of SpO2 is recommended.